MONTE CARLO SIMULATIONS OF Co (II) IN WATER INCLUDING THREE-BODY CORRECTION - Cahyorini Kusumawardani; Harno Dwi Pranowo; Crys Fajar Partana; Mudasir Mudasir (Indonesian Journal of Chemistry, 2006)
In order to describe the cobalt-water interaction correctly, a new ab initio potential was developed consisting of pair interaction terms as well as three-body contributions. Within this approach, it was possible to correct for the well-known failures of pair potentials in describing solvation phenomena of such ions. A first-shell coordination number of 6 in agreement with experimental data were obtained from Monte Carlo simulations of a single cobalt (II) ion in water. The structure of hydrated ion is discussed in terms of radial density functions and coordination number, energy and angular distributions.